2010
DOI: 10.1038/ejcn.2010.173
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial hyperglycemia and insulin response are affected by sea buckthorn (Hippophaë rhamnoides ssp. turkestanica) berry and its ethanol-soluble metabolites

Abstract: Background/Objectives: Repeated postprandial hyperglycemia and subsequent mild, late hypoglycemia as well as high postprandial insulin response lead to metabolic events that may eventually develop into type 2 diabetes. The aim of this study was to assess how sea buckthorn berries as well as two sea buckthorn extraction residues modulate the postprandial metabolism after a high-glucose meal. Subjects/Methods: Ten healthy normal-weight male volunteers consumed four study breakfasts, one control (A) and three sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Animal and in vitro studies have suggested that SBo (810) and alcohol extracts and flavonoid preparations (1114) have antioxidant and antiinflammatory activities and may beneficially affect serum glucose and triglyceride concentrations (15). These results have been supported by recent clinical studies (16, 17). …”
Section: Introductionsupporting
confidence: 81%
“…Animal and in vitro studies have suggested that SBo (810) and alcohol extracts and flavonoid preparations (1114) have antioxidant and antiinflammatory activities and may beneficially affect serum glucose and triglyceride concentrations (15). These results have been supported by recent clinical studies (16, 17). …”
Section: Introductionsupporting
confidence: 81%
“…Sea buckthorn flavones have been linked with inhibition of thrombosis and hypertension [16], [17], and promotion of wound healing [18]. The positive effects of berries and its extracts have also been demonstrated in human subjects [19], [20] thus, both historical accounts and scientific research indicate that this plant has immense nutritional and medicinal potential.…”
Section: Introductionmentioning
confidence: 99%
“…Sea buckthorn puree can lower the plasma high-sensitivity c-reactive protein level (Larmo et al 2008), which is a marker for inflammation and a risk factor for cardiovascular disease. Furthermore, ethanol-soluble components of sea buckthorn fruits have been shown to affect postprandial hyperglycemia and insulin response (Lehtonen et al 2010a) and the beneficial flavonols of sea buckthorn berries have proven to be highly bioavailable (Larmo et al 2009, Lehtonen et al 2010b). …”
Section: Introductionmentioning
confidence: 99%